Sharing is caring: How EM Sim Cases (EMSimCases.com) has created a collaborative simulation education culture in Canada. Issue 6 (November 2020) - Caners, Kyla; Baylis, Jared; Heyd, Christopher; Chan, Teresa
ABSTRACT: Free open access medical education (FOAM) resources in emergency medicine (EM) have grown exponentially in recent years. Within this movement, there are relatively few resources dedicated to simulation in EM. EM Sim Cases is a FOAM resource that was started in 2015 with the goal of creating a central database of simulation cases and scholarly articles that could be shared worldwide and thus reduce needless duplication of effort. Since 2015, EM Sim Cases has grown to have an annual average of 8, 148 views per month from a total of 161 countries. It has an editorial team of 18 members as well as a leadership team of three. There is a robust, peer-reviewed case bank ranging in topic from neonatal resuscitation to end-of-life care as well as a number of simulation-relevant educational posts.